Effects of Habitat Fragmentation on Effective Population Size in the Endangered Rio Grande Silvery Minnow - ALÒ, DOMINIQUE; TURNER, THOMAS F. (Conservation biology, 2005)
We assessed spatial and temporal patterns of genetic diversity to evaluate effects of river fragmentation on remnant populations of the federally endangered Rio Grande silvery minnow (Hybognathus amarus). Analysis of microsatellite and mitochondrial DNA detected little spatial genetic structure over the current geographic range, consistent with high gene flow despite fragmentation by dams. Maximum-likelihood analysis of temporal genetic data indicated, however, that present-day effective population size (NeV) of the largest extant population of this species was 78 and the ratio of effective size to adult numbers$(N_{eV}/N)$was$\sim 0.001$during the study period (1999 to 2001). Coalescent-based analytical methods provided an estimate of historical (river fragmentation was completed in 1975) effective size (NeI) that ranged between 105and 106. We propose that disparity between contemporary and historical estimates of Neand low contemporary Ne/N result from recent changes in demography related to river fragmentation. Rio Grande silvery minnows produce pelagic eggs and larvae subject to downstream transport through diversion dams. This life-history feature results in heavy losses of yearly reproductive effort to emigration and mortality, and extremely large variance in reproductive success among individuals and spawning localities. Interaction of pelagic early life history and river fragmentation has altered demographic and genetic dynamics of remnant populations and reduced Neto critically low values over ecological time.